Penggunaan Tenaga Kerja Keluarga Petani Peternak Itik pada Pola Usahatani Tanaman Padi Sawah di Kecamatan Air Hangat Kabupaten Kerinci - Fatati, Fatati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
TheÂ researchÂ wasÂ aimedÂ toÂ findÂ outÂ theÂ laborÂ employmentÂ fromÂ farmerÂ andÂ duck veterinarian family at farmer working pattern of rice plantation at Air Hangat Regency. The research was held by using survey method. The samples were 3 villages which were taken by purposive sampling method with determined criterion that the villages have main effort at rice plantationÂ as well as feeding ducks as secondary effort. The villages are Koto MajidinÂ HilirÂ Village,Â MajidinÂ MudikÂ VillageÂ andÂ TebatÂ IjukÂ Village.Â While,Â the respondents were the veterinarian who were chosen by using Simple Random Sampling Technique.Â TheÂ numberÂ ofÂ respondentsÂ isÂ determined proportionallyÂ basedÂ onÂ the population number of ducks at each village; there were 20 respondents at Majidin Hilir village, 15 respondents at Majidin Mudik village and 10 respondents at Tebat Ijuk village. The total number was 45 respondents. The research period is based on Effective Working timeÂ andÂ theÂ laborsÂ areÂ countedÂ basedÂ onÂ ManÂ BaseÂ Labor.Â Next,Â theÂ collectedÂ dataÂ is processed descriptively. The research result showed that the number of family labor was 57,39Â personsÂ perÂ plantÂ season,Â whileÂ theÂ familyÂ laborÂ whoÂ areÂ employedÂ wasÂ 50,69 persons per plant season. Thus the rest of family labor was 6,70 persons per plant season.